Πλάτων τρόπον τινὰ οὐ κακῶς τὴν σοφιστικὴν περὶ τὸ μὴ ὂν ἔταξεν (Aristot. Metaph. 1026b14) - Wesoły, Marian Andrzej (Peitho. Examina Antiqua, 2024)
Aristotle’s observation that “Plato not wrongly ordered sophistry around non-being” (Metaph. E 2, 1026b14; also in K 8, 1064b29) refers generally to Plato’s Sophist. The admission of non-being (τὸ μὴ ὄν) could be considered as a certain consequence of the Eleatic monism, which gave rise to the Sophistic movement as has been recognized by Plato and Aristotle. In this paper, we try to identify more precisely the context of this setting of non-being of polemical and very particular importance. Plato’s Sophist discusses non-being, but the inspiration came precisely from the audacious argument of an unnamed sophist who dares to challenge Parmenides’ solemn prohibition of non-being. In fact, the Stranger of Elea recounts that even as a boy he knew the prohibition of the great Parmenides (Soph. 237a). Moreover, being younger, he believed he understood exactly this difficulty, that is, when “someone” (τις) spoke of non-being; now he entangles himself in various aporias regarding this issue (Soph. 243b). Thus, it is the unnamed sophist, who “takes refuge in the darkness of non-being and attaches himself to it in its exercise, which is hard to grasp because the place is so dark” (Soph. 254a). The discussion that follows has a twofold purpose: first, against Parmenides’ prohibition, to admit non-being, and secondly, by refuting the sophist’s meontological argument, to propose a better solution. We observe that Plato in his polemic with a “sophist,” although in an allusive form and without ever explicitly naming Gorgias, but in such a way as to allow an implicit identification of him, draws nourishment from his “own demonstration” (ἴδιος ἀπόδειξις), which is based on the formula of identity, i.e., on the assertion that “non-being is non-being” (cf. De MXG, 979a25-33). Thus, the Elean Stranger (Soph. 258b-c), when arguing with the sophistic invention of non-being, has taken up the same tautological “is” that was coined by Gorgias in order to overturn the ontological argument of Parmenides, albeit his understanding in this regard was different from that of the Leontinian. This testifies to a positive qualification of non-being which in this way is not in absolute opposition to being, but is only different from it. This solution also allows Plato to solve the problem of negative predication and the statement of falsehood. Scholars of Plato do not suppose that the author of the Sophist could have had precisely the Sophist Gorgias in mind. But in our opinion, in this way the meaning of this difficult sentence (Soph. 258c) is clarified and it becomes evident which of the sophistic arguments Plato has in mind here. But it was none other than Gorgias who accepted the possibility of identities in expressions and used the refuting method to show that even that which is different is somehow identical and vice versa, and in particular that the identical is the opposite of being and of non-being (cf. Phaedr. 267a-b with reference to Gorgias). Plato, however, stopped only at the formulation of the meontological argument, unlike the sophist Gorgias, who proceeded further in the direction of ontological nihilism, consequently nullifying the possibility of λόγος, which is discussed in the next part of the Sophist (259d-260b), where the sophist Gorgias is criticized, though not named. The author of this paper has already presented the above theses in several Polish and Italian articles, but so far has not found a critical response in the literature on the subject.